Reduced order models of elastic glass plate under low velocity impact. (February 2021) - Janda, Tomáš; Schmidt, Jaroslav; Hála, Petr; Konrád, Petr; Zemanová, Alena; Sovják, Radoslav; Zeman, Jan; Šejnoha, Michal
Highlights: Response of glass plate to a low velocity impact is analyzed. Three types of simplified numerical models are introduced. Models are verified against industry standard finite element software. Models are validated against experimental data of two different glass plates. Accuracy depends on the plate dimensions and the impactor stiffness. Abstract: This article concerns numerical simulations of glass plates loaded by a force impulse caused by a low velocity impact. Three types of numerical models of different complexity – the spring-mass system, the modal decomposition based model, and the conventional finite element method – all exploiting the Hertz contact law are compared and their advantages and limitations are discussed. Their performance is verified against the results provided by the commercial software LS-DYNA and validated by two full scale experiments. It is observed that the accuracy of the spring-based model decreases with increasing dimension of the plate and increasing stiffness of the impactor. Nevertheless, the models based on modal decomposition and finite element methods deliver results reasonably close to experimental measurements.